A graphite oxide negative electrode and its preparation method and application
By creating pores on the surface and internal surface of graphite oxide and doping N elements, a graphite oxide negative electrode with a nanoporous structure was prepared, which solved the problem of long diffusion path of the graphite negative electrode, and achieved large-scale charge and discharge and efficient contact.
Patent Information
- Application Number
- CN202410154725.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-02-04
AI Technical Summary
As the negative electrode material of sulfide-based solid-state battery, graphite has a long diffusion path of lithium ions, which makes it difficult to achieve large-scale charging and discharging.
Pores are made by oxygen-oxide-based graphite oxide surface, strong alkali is used to oxidize and etch the inside of the graphite to create pores, and dopant N elements at high temperatures to prepare a graphite oxide negative electrode with a nanoporous structure.
The diffusion path of lithium ions is shortened, the diffusion rate of lithium ions is increased, the charging and discharging of large ratios is achieved, and the effective contact between the sulfide electrolyte and graphite is enhanced.
Smart Images

Figure CN117936697B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery negative electrode materials, and particularly relates to a graphite oxide negative electrode and a preparation method and application thereof. Background Art
[0002] Solid-state batteries have become a hot research topic for the next generation of lithium-ion batteries because they use non-flammable and easy-to-process solid electrolytes and can simultaneously achieve high safety and high energy density requirements. There are three main types of solid-state battery electrolytes: polymer-based, oxide-based, and sulfide-based. Among them, sulfide-based solid-state batteries have high ionic conductivity comparable to liquid batteries, as well as good laminate pressure mechanical properties, making them the most likely solid-state batteries to be commercialized. Graphite has been successfully used in lithium-ion batteries since 1901 and is still the most successful commercialized lithium-ion battery negative electrode material with good cycle stability. However, as a sulfide-based solid-state battery negative electrode material, it still faces huge challenges. The graphite lithium insertion process is that lithium ions enter the layer from the end face, the transmission path is long, and high-rate charging and discharging is difficult to achieve.
[0003] Therefore, there is an urgent need to provide a new negative electrode material to increase the diffusion rate of lithium ions and achieve high-rate charging and discharging. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a graphite oxide negative electrode and a preparation method and application thereof. The graphite oxide negative electrode of the present invention can shorten the diffusion path of lithium ions, thereby increasing the diffusion rate of lithium ions and realizing high-rate charge and discharge.
[0005] The present invention firstly oxidizes the graphite surface with oxygen to produce pores on the graphite surface, then uses a strong alkali to oxidize and etch the inside of the graphite to produce pores, and finally performs high-temperature doping of the N element, which can not only shorten the diffusion path of lithium ions, thereby increasing the diffusion rate of lithium ions and realizing high-rate charging and discharging, but also is conducive to increasing the effective contact between the sulfide electrolyte powder and the graphite.
[0006] A first aspect of the present invention provides a graphite oxide negative electrode.
[0007] Specifically, a graphite oxide negative electrode has a nanoporous structure and contains O and N.
[0008] Preferably, the nanoporous structure is located on the surface and inside of the graphite oxide negative electrode.
[0009] Preferably, the pore size of the nanoporous structure is 1-50 nm, more preferably 5-20 nm, and more preferably, the average pore size of the nanoporous structure is 12-13 nm.
[0010] Preferably, the specific surface area of the graphite oxide negative electrode is 12.8-15.0m 2 / g, more preferably 12.83-14.5m 2 / g.
[0011] Preferably, the content of O is 6-16wt%, more preferably 8-15wt%.
[0012] Preferably, the N content is 2-12 wt %, more preferably 3-10 wt %.
[0013] A second aspect of the present invention provides a method for preparing a graphite oxide negative electrode.
[0014] Specifically, a method for preparing a graphite oxide negative electrode comprises the following steps:
[0015] (1) subjecting graphite to oxidation treatment in an oxidizing gas atmosphere to obtain graphite oxide having pores on the surface;
[0016] (2) etching and oxidizing the graphite oxide with pores on the surface of step (1) using a strong alkaline solution to obtain graphite oxide with pores inside;
[0017] (3) The graphite oxide containing pores inside is dried and then heat treated in a nitrogen atmosphere to obtain the graphite oxide negative electrode.
[0018] Preferably, in step (1), the graphite is natural graphite or mesophase carbon microbeads, and more preferably natural graphite.
[0019] Preferably, in step (1), the oxidizing gas comprises a mixed gas of oxygen and nitrogen, and the mixed gas further preferably comprises an oxygen volume fraction of 20-35%.
[0020] Preferably, in step (1), the volume content of oxygen in the oxidizing gas is 15-35%, more preferably 20-30%.
[0021] Preferably, in step (1), the temperature of the oxidation treatment is 780-850°C, more preferably 800-850°C.
[0022] Preferably, in step (1), the heating rate during the oxidation treatment is 4-8°C / min, more preferably 5-6°C / min.
[0023] Preferably, in step (1), the oxidation treatment time is 0.5-1.5 hours, more preferably 1-1.2 hours.
[0024] Preferably, in step (2), the strong alkaline solution is a NaOH solution or a KOH solution.
[0025] Preferably, in step (2), the concentration of the strong alkaline solution is 3-5 mol / L, more preferably 3-4 mol / L.
[0026] Preferably, in step (3), the drying temperature is 80-90° C. and the drying time is 10-12 hours.
[0027] Preferably, in step (3), the temperature of the heat treatment is 800-850°C, more preferably 820-850°C.
[0028] Preferably, in step (3), the heating rate during the heat treatment is 4-8°C / min, more preferably 5-6°C / min.
[0029] Preferably, in step (3), the heat treatment time is 3-4 hours, more preferably 3.5-4 hours.
[0030] The first stage of graphite oxidation can be obtained by first treating the surface of graphite with oxygen. By controlling a certain amount of oxygen, the smooth graphite surface can be treated to a rough and porous structure. Then the second stage of strong alkali oxidation is carried out. The NaOH solution can enter the graphite through the pores obtained by the first stage of oxidation, and then etch and form pores inside. The heat treatment is to remove the excess strong alkali solution and dope the N element at high temperature. In summary, the transmission path of lithium ions can be shortened, and it is also beneficial to increase the effective contact between the sulfide electrolyte powder and the graphite.
[0031] A third aspect of the present invention provides an application of a graphite oxide negative electrode.
[0032] Specifically, a battery includes the above-mentioned graphite oxide negative electrode, positive electrode, and electrolyte.
[0033] Preferably, the electrolyte is a sulfide solid electrolyte.
[0034] Optionally, the graphite oxide negative electrode is used as the negative electrode of a lithium-ion liquid battery.
[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0036] (1) The graphite oxide negative electrode of the present invention contains a nanoporous structure and is doped with N element, which can not only shorten the diffusion path of lithium ions, thereby increasing the diffusion rate of lithium ions and achieving high-rate charge and discharge, but also help to increase the effective contact between sulfide electrolyte powder and graphite.
[0037] (2) The present invention first uses oxygen to oxidize the graphite surface to create pores on the graphite surface, then uses a strong base to oxidize and etch the inside of the graphite to create pores, and finally high-temperature doping of the N element is performed. This can not only shorten the diffusion path of lithium ions, thereby increasing the diffusion rate of lithium ions and achieving high-rate charge and discharge, but also help to increase the effective contact between the sulfide electrolyte powder and the graphite.
[0038] (3) The present invention provides a method for forming pores on the surface and inside of graphite oxide, which achieves the result of reducing costs and increasing efficiency. By controlling the oxygen content and the oxidation temperature, a certain degree of oxidation can be carried out on the graphite surface, so that pores can appear on the graphite surface; then the second stage of internal strong alkali etching oxidation is carried out; in addition, high-temperature N doping is carried out. This method can shorten the transmission path of lithium ions from the graphite surface to the inside, increase the diffusion rate of lithium ions, and achieve charge and discharge performance under high-rate current density; in addition, oxidation can cause part of the graphite layer to peel off and form part of the graphene-like material, greatly improving the reversible capacity of the graphite; and the N element contains lone pairs of electrons, which can form a conjugated effect with the large π bonds of the carbon atom lattice, and has a certain improvement effect on the electrochemical performance. In summary, the graphite oxide negative electrode prepared by the present invention has excellent stability for sulfide solid-state batteries, which is of great significance for achieving high-rate performance and safe sulfide solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a BET (specific surface area) diagram of the graphite oxide negative electrode of Example 1 of the present invention;
[0040] Figure 2 It is a GITT diagram of a sulfide solid-state button battery prepared using the graphite oxide negative electrode of Example 1 of the present invention;
[0041] Figure 3 This is a 2C second cycle charge and discharge curve of the sulfide solid-state button battery prepared with graphite oxide negative electrode in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0043] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0044] Example 1: Preparation of graphite oxide negative electrode
[0045] A method for preparing a graphite oxide negative electrode comprises the following steps:
[0046] 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 30% (volume fraction) was introduced, and the temperature was raised to 850° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A;
[0047] The cooled graphite oxide A was placed in a beaker containing 100 mL of 3 mol / L NaOH solution, stirred magnetically at 400 rpm for 6 h, and then centrifuged three times to obtain the second-stage graphite oxide B;
[0048] The graphite oxide B is dried and vacuum dried at 80° C. for 12 h to obtain dried graphite oxide C;
[0049] The dried graphite oxide C was heat treated under the following conditions: in a nitrogen atmosphere, the temperature was raised from room temperature to 850°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain a graphite oxide negative electrode.
[0050] Example 2: Preparation of graphite oxide negative electrode
[0051] A method for preparing a graphite oxide negative electrode comprises the following steps:
[0052] 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 21% (volume fraction) was introduced, and the temperature was raised to 850° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A;
[0053] The cooled graphite oxide A was placed in a beaker containing 100 mL of 3 mol / L NaOH solution, stirred magnetically at 400 rpm for 6 h, and then centrifuged three times to obtain the second-stage graphite oxide B;
[0054] The graphite oxide B is dried and vacuum dried at 80° C. for 12 h to obtain dried graphite oxide C;
[0055] The dried graphite oxide C was heat treated under the following conditions: in a nitrogen atmosphere, the temperature was raised from room temperature to 850°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain a graphite oxide negative electrode.
[0056] Example 3: Preparation of graphite oxide negative electrode
[0057] A method for preparing a graphite oxide negative electrode comprises the following steps:
[0058] 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 30% (volume fraction) was introduced, and the temperature was raised to 800° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A;
[0059] The cooled graphite oxide A was placed in a beaker containing 100 mL of 3 mol / L NaOH solution, stirred magnetically at 400 rpm for 6 h, and then centrifuged three times to obtain the second-stage graphite oxide B;
[0060] The graphite oxide B is dried and vacuum dried at 80° C. for 12 h to obtain dried graphite oxide C;
[0061] The dried graphite oxide C was heat treated under the following conditions: in a nitrogen atmosphere, the temperature was raised from room temperature to 850°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain a graphite oxide negative electrode.
[0062] Example 4: Preparation of graphite oxide negative electrode
[0063] A method for preparing a graphite oxide negative electrode comprises the following steps:
[0064] 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 30% (volume fraction) was introduced, and the temperature was raised to 850° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A;
[0065] The cooled graphite oxide A was placed in a beaker containing 100 mL of 4 mol / L NaOH solution, and magnetically stirred at 400 rpm for 6 h, followed by centrifugation three times to obtain the second-stage graphite oxide B.
[0066] The graphite oxide B is dried and vacuum dried at 80° C. for 12 h to obtain dried graphite oxide C;
[0067] The dried graphite oxide C was heat treated under the following conditions: in a nitrogen atmosphere, the temperature was raised from room temperature to 850°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain a graphite oxide negative electrode.
[0068] Example 5: Preparation of graphite oxide negative electrode
[0069] A method for preparing a graphite oxide negative electrode comprises the following steps:
[0070] 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 30% (volume fraction) was introduced, and the temperature was raised to 850° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A;
[0071] The cooled graphite oxide A was placed in a beaker containing 100 mL of a 3 mol / L KOH solution, and magnetically stirred at 400 rpm for 6 h, followed by centrifugation three times to obtain the second-stage graphite oxide B.
[0072] The graphite oxide B is dried and vacuum dried at 80° C. for 12 h to obtain dried graphite oxide C;
[0073] The dried graphite oxide C was heat treated under the following conditions: in a nitrogen atmosphere, the temperature was raised from room temperature to 800°C at a heating rate of 5°C / min and kept at that temperature for 4 hours to obtain a graphite oxide negative electrode.
[0074] Comparative Example 1
[0075] A method for preparing a graphite oxide negative electrode comprises the following steps:
[0076] 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 30% (volume fraction) was introduced, and the temperature was raised to 850° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A;
[0077] The first-stage graphite oxide A was heat-treated under the following conditions: in a nitrogen atmosphere, the temperature was raised from room temperature to 850° C. at a heating rate of 5° C. / min and kept at that temperature for 4 h to obtain graphite oxide.
[0078] Comparative Example 2
[0079] A method for preparing a graphite oxide negative electrode comprises the following steps:
[0080] 10 g of natural graphite was weighed and placed in a beaker containing 100 mL of 3 mol / L NaOH solution, and magnetically stirred at 400 rpm for 6 h, followed by centrifugation three times to obtain graphite oxide B;
[0081] The graphite oxide B is dried and vacuum dried at 80° C. for 12 h to obtain dried graphite oxide C;
[0082] The dried graphite oxide C was heat treated under the following conditions: in a nitrogen atmosphere, the temperature was increased from room temperature to 850° C. at a heating rate of 5° C. / min and kept at that temperature for 4 h to obtain graphite oxide.
[0083] Comparative Example 3
[0084] A method for preparing a graphite oxide negative electrode comprises the following steps:
[0085] 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 30% (volume fraction) was introduced, and the temperature was raised to 850° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A;
[0086] The cooled graphite oxide A was placed in a beaker containing 100 mL of 3 mol / L NaOH solution, stirred magnetically at 400 rpm for 6 h, and then centrifuged three times to obtain the second-stage graphite oxide B;
[0087] The graphite oxide B was dried and vacuum dried at 80° C. for 12 h to obtain graphite oxide C.
[0088] Product effect testing
[0089] The graphite oxide prepared in the comparative example and the embodiment was taken to test its first coulomb efficiency and the second cycle charge and discharge performance. The method for preparing the sulfide solid button battery is as follows: the prepared graphite oxide is ground together with the electrolyte LiP6S5Cl, and then the binder PTFE (polytetrafluoroethylene) is added, and the round pieces are cut into 10mm diameter after grinding evenly again, and then put into a mold, and the electrolyte LiP6S5Cl is added. The electrode is a Li-In alloy, and the whole is pressed at a pressure of 450MPa to obtain a solid-state battery electrode, and then stainless steel gaskets are added at both ends of the solid-state battery electrode, and a nickel mesh shrapnel is added on one side, and packaged to obtain a solid-state button battery. The test pressure is 5MPa. The charge and discharge range is -0.61-1.0V, the charge and discharge ratio of the first cycle is 0.1C, and the charge and discharge ratio of the second cycle is 2C. The test results are shown in Table 1:
[0090] Table 1
[0091] First coulombic efficiency (%) Discharge capacity at 2C (mAh / g) Example 1 93.5% 286.4 Example 2 92.1% 244.3 Example 3 91.7% 237.4 Example 4 92.2% 239.7 Example 5 92.8% 271.2 Comparative Example 1 89.3% 214.0 Comparative Example 2 90.0% 200.8 Comparative Example 3 93.0% 198.6
[0092] It can be seen from Table 1 that, compared with Comparative Examples 1-3, when the graphite oxide negative electrode prepared in Examples 1-5 of the present invention is used as the negative electrode of the solid-state battery, the battery has a better high-rate charge and discharge specific capacity.
[0093] Figure 1 This is the BET diagram of the graphite oxide negative electrode of Example 1 of the present invention; Figure 2 It is a GITT diagram of a sulfide solid-state button battery prepared using the graphite oxide negative electrode of Example 1 of the present invention; Figure 3 This is a 2C second cycle charge and discharge curve of the sulfide solid-state button battery prepared with graphite oxide negative electrode in Example 1 of the present invention.
[0094] Figure 1 ( Figure 1 "Volume adsorbed" means adsorption volume, "Relative Pressure" means relative pressure, "Adsorption" means adsorption, "Desorption" means desorption, "Pore" means pore, and "Pore width" means pore width) is the result of nitrogen adsorption and desorption. Figure 1 The average pore size of the porous graphite oxide negative electrode in Example 1 is about 12.44 nm. The internal part of the graphite oxide negative electrode also has a porous structure through etching with NaOH solution. The specific surface area of the graphite oxide negative electrode in Example 1 is 12.83 m2 / g. In the subsequent GITT (constant current intermittent titration method) test, it can be seen that the Li + Diffusion coefficient diagram Figure 2 ( Figure 2 The vertical axis represents the lithium ion diffusion coefficient, and the horizontal axis "Voltage" represents the voltage). As shown in the figure, the entire curve presents a "W" shape. The range of the lithium ion diffusion coefficient is 10 -12 -10 -8 cm 2 s -1 .from Figure 3 ( Figure 3 (“Voltage” represents voltage, and the horizontal axis “Capacity” represents capacitance) It can be seen that the discharge capacity of the solid-state battery prepared in Example 1 at a large rate of 2C is quite considerable, which is 286.4 mAh / g, and the coulombic efficiency is 99.3%.
Claims
1. A graphite oxide negative electrode, characterized in that The graphite oxide negative electrode has a nanoporous structure and contains O and N; The content of O is 6-16wt%; the content of N is 2-12wt%; The specific surface area of the graphite oxide negative electrode is 12.83 m 2 / g; The method for preparing the graphite oxide negative electrode comprises the following steps: 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 30% by volume was introduced, and the temperature was raised to 850° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A; The cooled graphite oxide A was placed in a beaker containing 100 mL of 3 mol / L NaOH solution, and magnetically stirred at 400 rpm for 6 h, followed by centrifugation three times to obtain the second-stage graphite oxide B. The graphite oxide B is dried and vacuum dried at 80° C. for 12 h to obtain dried graphite oxide C; The dried graphite oxide C was heat treated under the following conditions: in a nitrogen atmosphere, the temperature was increased from room temperature to 850°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain a graphite oxide negative electrode.
2. The graphite oxide negative electrode according to claim 1, characterized in that The nanoporous structure is located on the surface and inside of the graphite oxide negative electrode.
3. The graphite oxide negative electrode according to claim 1, characterized in that The average pore diameter of the nanoporous structure is 12.44 nm.
4. The method for preparing a graphite oxide negative electrode according to any one of claims 1 to 3, characterized in that: The following steps are involved: 10 g of natural graphite was weighed and placed in a rotary heating furnace, and a mixed gas of oxygen and nitrogen with an oxygen content of 30% by volume was introduced, and the temperature was raised to 850° C. at a heating rate of 5° C. / min, and high-temperature oxidation was performed at this temperature for 1 h to obtain the first-stage oxidized graphite A; The cooled graphite oxide A was placed in a beaker containing 100 mL of 3 mol / L NaOH solution, stirred magnetically at 400 rpm for 6 h, and then centrifuged three times to obtain the second-stage graphite oxide B; The graphite oxide B is dried and vacuum dried at 80° C. for 12 h to obtain dried graphite oxide C; The dried graphite oxide C was heat treated under the following conditions: in a nitrogen atmosphere, the temperature was increased from room temperature to 850°C at a heating rate of 5°C / min and kept warm for 4 hours to obtain a graphite oxide negative electrode.
5. A battery, characterized in that: It comprises the graphite oxide negative electrode, positive electrode and electrolyte as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Preparation method of high-magnification artificial graphite negative electrode material
CN111584866A
Negative electrode carbon material for lithium secondary battery, negative electrode for lithium battery, and lithium secondary battery
JP2014199750A